Trade facilitation and trade participation: Are sub-Saharan African firms different? - Abdoulaye Seck (Journal of African Trade, 2016)
Sub-Saharan Africa is the region where firms face the greatest hurdles when it comes to cross-border trading. This paper examines how these firms, relative to their counterparts in the developing world, would respond to changes in the trade environment as a result of trade facilitation reforms. Using data from World Bank's Enterprise Surveys, the paper suggests that improving customs clearance, government regulations, trade finance, and energy and telecommunication infrastructure contributes to increasing the probability of firms' entry into exporting and importing, as well as to the extent of their trade. The results also indicate that African firms tend to respond more to a changing environment, owing to the greater constraints that they face. Exports tend to be more responsive than imports, suggesting a favorable short-term adjustment of the balance of payments. There is a sizable distributive effect, as larger and smaller firms gain differently depending on which reform and which direction of trade one considers. These results could help better understand how to harness the trade potential of sub-Saharan African firms, and they should constitute a welcome addition to the body of knowledge at a time when there is an uncertainty about the priority issues for multilateral agreements in the area of trade.
Keywords: F13; F15; O24; 330; Trade facilitation; Exports; Imports; Firms; Sub-Saharan Africa